2016
DOI: 10.3762/bjoc.12.123
|View full text |Cite
|
Sign up to set email alerts
|

Copper-catalyzed [3 + 2] cycloaddition of (phenylethynyl)di-p-tolylstibane with organic azides

Abstract: SummaryTrisubstituted 5-stibano-1H-1,2,3-triazoles were synthesized in moderate to excellent yields by the Cu-catalyzed [3 + 2] cycloaddition of a ethynylstibane with organic azides in the presence of CuBr (5 mol %) under aerobic conditions. The reaction of 5-stibanotriazole with HCl, I2, and NOBF4 afforded 1-benzyl-4-phenyltriazole, 1-benzyl-5-iodo-4-phenyltriazole, and a pentavalent organoantimony compound, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…However, the reaction with aryl azides such as 4‐methylphenyl and 4‐cyanophenyl azides gave complex mixtures. We have recently reported that 5‐stibanotriazoles could not be obtained by the Cu‐catalysed [3+2] cycloaddition of (phenylethynyl)di‐ p ‐tolylstibane with aryl‐azides . Even in the three‐component reaction, there might be a problem with the cyclization step.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the reaction with aryl azides such as 4‐methylphenyl and 4‐cyanophenyl azides gave complex mixtures. We have recently reported that 5‐stibanotriazoles could not be obtained by the Cu‐catalysed [3+2] cycloaddition of (phenylethynyl)di‐ p ‐tolylstibane with aryl‐azides . Even in the three‐component reaction, there might be a problem with the cyclization step.…”
Section: Resultsmentioning
confidence: 99%
“…Based on the above control experiments, a possible mechanism for this three‐component reaction is shown in Scheme . The reaction involves the formation of 5‐stibanotriazole 7 from ethynylstibane 1 and azide 2 in the presence of a Cu catalyst ,. [17b] Also, diaryl diselenide 3 reacts with bimetallic complex [(phen) 2 CuI 2 ] A to generate Cu III intermediate B .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yasuike's group reported the Cu‐catalyzed [3+2] cycloaddition of phenyl ethynylstibane with organic azides in the presence of CuBr (5 mol%) under aerobic conditions leading to trisubstituted 5‐stibano 1,2,3‐triazoles 61 . The treatment of I 2 with the 5‐stibanotriazole reacted smoothly to afford the 1‐benzyl‐5‐iodo‐4‐phenyl‐triazole 62 with a moderate yield [59] . In addition, the same group performed the formation of the 5‐iodo‐triazole by antimony (Sb) – lithium (Li) exchange reaction.…”
Section: The Synthesis Of 5 and 4‐halo‐123‐triazoles By [3+2] Cycloadditionmentioning
confidence: 99%
“…Yasuike et al. investigated the performance of 1‐stibanolalkynes 21 in CuA I AC (Scheme 10b) [23] . In the presence of copper(I) bromide, 5‐stibano triazoles 22 could be prepared in up to 91% yield.…”
Section: Transition Metal‐catalyzed Cycloaddition Of Azides With Inte...mentioning
confidence: 99%